INVESTIGASI DAN MITIGASI STRUKTUR BANGUNAN SEKOLAH AKIBAT GEMPA BUMI CIANJUR - Kristianto, Anang; Wiyono, Daud R; Setiawan, Deni; Suhendra, Andrias; Pranata, Yosafat Aji (Servirisma, 2023)
Earthquakes are unexpected natural disasters that can cause severe damage to buildings, especially those not compliant with standards. The construction of educational facilities, in this case, school buildings in Indonesian territory located in earthquake-prone areas, needs special attention. The Cianjur earthquake that occurred in 2022 resulted in damage to several school buildings in the affected area. The Community Service activities in this article investigate 9 Junior High School buildings and 5 Elementary School buildings in the Cianjur Regency area that experienced minor to severe damage that must be immediately repaired or strengthened. Community service in cooperation with the Cianjur regional government's educational institutions and school personnel impacted by the earthquake. The results of the visual investigation of the school building show damage from moderate to severe levels and require immediate action, considering that Cianjur has a high earthquake risk. Repairs and strengthening can be carried out according to the damage level, starting from adding new columns for beams that experience excessive deflection due to dimensions that do not meet the requirements or adding reinforcement using FRP. Columns with dimensions that do not meet the requirements, dimensions can be added even if there is no significant damage visually during the investigation.